(3NdGUI GdhaG HCNHGQ OGQ GdeUWais - (3Ydj Hf YHO Gddg Hf CMeO GdMSfj GdSeghOj GdeOfj GdTGaYj ,CHh GdMSf fhQ GdOjf,J (B911 (3g` s ((3GdMSfi Hf eMeO GdHcQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa WGHI , hTQa GdbdhH dSeGY CNHGQgG GdeSJWGHI hHYO , abO TZaJ HCNHGQ GdMHjHI GdeMHI aCdaJ ai Pdc cJGHkG cGedkG SejJg GdhaG HCNHGQ OGQ GdeUWai Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3ef MQa GdjGA , bhdg ceG bGd GdgLQi , hgj efGRd CSde ceG ChVMfGg bGd GdgLQi (B: (3heeQjjf WQjb JSdc gfGc Edi jjf , hGddg JYGdi CYde HGdUhGH s
(3hVYg eDdag YGe (B893 (3g`s
(3HgG HYV GdWeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs